Development analysis of Mortiño (Vaccinium meridionale Swart.) plants derived from clonal and sexual propagation (2015)
A research was carried out at Corpoica´s La Selva,Experiment Station located at Rionegro, Antioquia,Colombia, at 2.120 masl in the ecological zone Low Mountain Rain Forest. The objective was to characterize growth and development of andean blueberry Vaccinium meridionale Sw., plants, obtained by seed and clonal propagation, from a wild population of the species. Four plants of each type were transplanted to rizhotrons, with glasses on two sides, which allowed the root growth recording. The plants coming from seed spent 1.663 days from sowing to flowering, and those derived from rooted cuttings 1.367 days. In both types, the roots lack root hairs. Also, in both kinds of materials, there was evidence for non alternating periods of root and aerial organs growth, with 6.28 and 7.00 as allometric indexes between the aerial part and the roots for the individuals obtained by sexual and asexual propagation. In spite of the occurrence of periods of increased flower production, after the beginning of the flowering to the end of the research,these organs were detected in both types of materials.There was a greater interplant variability in the growth values obtained in the sexual plants than those of the clonal ones.